An analysis of springback of compliant assemblies by contact modeling and welding distortion - Atik, Hafsa; Chahbouni, Mouhssine; Amagouz, Driss; Boutahari, Said (International Journal of Engineering and Technology, 2018)
Due to the development of the automotive and aeronautical industries, and the impossibility of pro-typing of the flexible parts because of the large real dimension as well as the behavior of this type of parts during the assembly, the tolerance of the flexible parts becomeÂ  an essential step in aeronautical manufacturing. Therefore the tolerance of plates in the assembly of mechanical systems is one of the key stages in the creation of a product in the automotive and aeronautical industries. This paper deals in the first stage a presentation of the tolerance of deformable mechanisms, through the illustration of the general problem. In order to study in the second stage the model of simulation of the variation of deformable (flexible) mechanisms, using the Influence Coefficient Method taking into account the effects of contact between the surface and including welding distortion. Finally the modeling of a mechanism of this type through an example with a view to an analysis of tolerances.Â